Caring for People Living With Dementia in Saudi Arabia: The Perspective of Nurses as Primary Caregivers - Loujain Sharif PhD; Sara Yaghmour PhD; Nariman AlKaf BSN; Rozan Fageera BSN; Layla Alotaibi BSN; Moroj Attar BSN; Abdulraheem Almutairy MSc; Khalid Sharif MD; Alaa Mahsoon PhD (SAGE Publishing, 2024)
Dementia is a progressive condition and an umbrella term used to describe a set of symptoms that affects many older adults. Older adults living with dementia often experience social stigma, which can impact their quality of life. Most people with dementia need the assistance of a caregiver in order to enhance their health. The present study seeks to explore the perspective of nurses as the primary caregivers of people living with dementia in Saudi Arabia, focusing on the challenges faced by nurses and their reactions to these challenges. A descriptive qualitative approach using semi-structured interviews with 10 nurses with experience caring for people living with dementia from 2 hospitals in Jeddah, Saudi Arabia. Using thematic analysis, 4 main themes were identified: (1) types of support, (2) challenges when caring for people living with dementia, (3) society's views on people living with dementia, and (4) nurses' perceptions of dementia. The nurses stated that people living with dementia do not receive sufficient support from their families. Most participants believed that public awareness about dementia is insufficient. Increased efforts to raise public awareness about dementia could include harnessing social norms around family structure and respect for elders to improve care provided to people living with dementia.